2022
DOI: 10.1002/1873-3468.14271
|View full text |Cite
|
Sign up to set email alerts
|

Ergothioneine in the brain

Abstract: Edited by Barry HalliwellErgothioneine (ERGO) is a naturally occurring food-derived antioxidant. Despite its extremely hydrophilic properties, ERGO is easily absorbed from the gastrointestinal tract and distributed to various organs, including the brain. This is primarily because its entry into brain cells is mediated by the ERGO-specific transporter OCTN1/SLC22A4. Octn1 gene knockout mice do not have ERGO in the brain, due to the absence of OCTN1 in neurons, neural stem cells, and microglia. The existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Notably, EGT shows high blood-brain barrier permeability and possesses neuroprotective effects, which are associated with the expression of OCTN1 ( Nakamichi et al, 2012 ). The regulation of cellular functions by EGT has been found in neurons, neural stem cells, microglia, and cerebral vascular endothelial cells ( Ishimoto and Kato, 2022 ; Nakamichi et al, 2022 ). Recent experimental studies have shown that supplementation of EGT (2 or 8 mg/kg/day) for 58 days significantly restores EGT levels in brain tissues, prevents memory and learning impairment, and alleviates body weight loss induced by cisplatin ( Song et al, 2010 ).…”
Section: Natural Products For the Treatment Of Crcimentioning
confidence: 99%
“…Notably, EGT shows high blood-brain barrier permeability and possesses neuroprotective effects, which are associated with the expression of OCTN1 ( Nakamichi et al, 2012 ). The regulation of cellular functions by EGT has been found in neurons, neural stem cells, microglia, and cerebral vascular endothelial cells ( Ishimoto and Kato, 2022 ; Nakamichi et al, 2022 ). Recent experimental studies have shown that supplementation of EGT (2 or 8 mg/kg/day) for 58 days significantly restores EGT levels in brain tissues, prevents memory and learning impairment, and alleviates body weight loss induced by cisplatin ( Song et al, 2010 ).…”
Section: Natural Products For the Treatment Of Crcimentioning
confidence: 99%
“…34,35 Experimental studies indicate that ergothioneine plays a beneficial role in the learning and memory of mice by preventing Aβ accumulation. [34][35][36][37] Moreover, vitamin D included in mushrooms may also show a beneficial effect on cognitive performance. 38,39 These studies suggested that mitigation of the risk of MCI may be attributed to the composition of protective effects of various nutrients from mushrooms.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Indeed, the interest around ERG is often focused on its ability to overcome neurotoxicity, usually induced by excess ROS. The role of ERG in the brain has already been reviewed a few times, most recently by Ishimoto and Kato [ 168 ] in their review titled “Ergothioneine in the brain”. Besides the excellent description of ERG, they also suggested a role for ERG in certain diseases of the central nervous system.…”
Section: Modulation Of Autophagy By Nutraceuticals: Support For the T...mentioning
confidence: 99%